2020
DOI: 10.1111/jfb.14274
|View full text |Cite
|
Sign up to set email alerts
|

Claudins of sea lamprey (Petromyzon marinus) – organ‐specific expression and transcriptional responses to water of varying ion content

Abstract: The role of lamprey epithelium tight junctions (TJs) in the regulation of salt and water balance is poorly understood. This study reported on claudin (Cldn) TJ protein transcripts of pre‐metamorphic larval and post‐metamorphic juvenile sea lamprey (Petromyzon marinus) and the transcriptional response of genes encoding Cldns to changed environmental ion levels. Transcripts encoding Cldn‐3b, ‐4, ‐5, ‐10, ‐14, ‐18 and ‐19 were identified, and mRNA expression profiles revealed the organ‐specific presence of cldn‐5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…It is known that tight junction (TJ) complexes dynamically control paracellular permeability in many vertebrate epithelia, including changes in gill epithelium of teleost fishes from “tight” in FW to “leaky” in SW 35 . A functional role for TJ complex proteins has more recently been elucidated in the sea lamprey 35 38 . Several studies have demonstrated putative corticosteroid control of TJ proteins in cultured teleost fish gill epithelia 24 , 39 , 40 , and it is possible that S may thus also control TJ complexing and paracellular permeability in the sea lamprey gill, in addition to its role in controlling active ion transport.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that tight junction (TJ) complexes dynamically control paracellular permeability in many vertebrate epithelia, including changes in gill epithelium of teleost fishes from “tight” in FW to “leaky” in SW 35 . A functional role for TJ complex proteins has more recently been elucidated in the sea lamprey 35 38 . Several studies have demonstrated putative corticosteroid control of TJ proteins in cultured teleost fish gill epithelia 24 , 39 , 40 , and it is possible that S may thus also control TJ complexing and paracellular permeability in the sea lamprey gill, in addition to its role in controlling active ion transport.…”
Section: Discussionmentioning
confidence: 99%
“…3A). Previous studies have provided evidence identifying the ocln gene as an osmoregulation-related gene in Acipenser baerii [51], while the cldn19 gene played significant roles in osmoregulatory physiology of Petromyzon marinus [52]. Moreover, the PSG cldn10, which predominantly expressed in osmoregulatory organs of teleost fishes [38,53], was found have two specific AA replacements in the two Pseudaspius species (Additional file 2: Figure S6A).…”
Section: Discussionmentioning
confidence: 94%
“…Certain claudin-10 isoforms are thought to provide the paracellular pathway with cation selective pores, which facilitate ion efflux in SW (Marshall et al, 2018). However, Kolosov et al (2020) recently demonstrated that claudin-10 is downregulated following SW acclimation in the lamprey, indicating that the contribution of claudins to epithelial barrier function may be species dependent.…”
Section: Regional Differences In Skin Functions and Effect Of Salinitymentioning
confidence: 99%